STRAIN GAUGE SENSOR OF MASS MEASUREMENT USING A BRASS CANTILEVER - Ayu, Hena Dian; Jufriadi, Akhmad; Pranata, Kurriawan Budi; E., Endarko; Muntini, Melania Suweni (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2017)
A study of mass measurement using strain gauge 120 which was placed in the corner of the brass cantilever has been done. This study essentially utilizes deflection phenomena on the surface. This phenomenon occurs due to the mass placed on one end of the brass cantilever. The Mass was calibrated with standard mass gauge using OHAUS PA214 PioneerTM analytical balance. It was done a variation of mass-reduction and addition at the end of the brass cantilever with a multiple of 0.1 gram over a span interval of 1.1-7.5 grams. It obtained hysteresis curve plot for the changing strain gauge resistance (ΔR) versus mass variations on which the system has the maximum load range (7,1-7,5 gram). Moreover, The test of the system for the mass variations in the output voltage of the IC AD521JD differential amplifier was approximated as a quadratic function which was expressed in the system characteristic equation m = 2,4×V2 - 0,8533×V + 1,1449, with m (gram) and V (Volt). The characteristic equation is used in the ADC conversion of the microcontroller. The measured mass value was displayed on 2 × 16 LCDs in grams.